Towards Extended Reality in Emergency Response: Guidelines and Challenges for First Responder Friendly Augmented Interfaces - Oztank, Fatih; Balcisoy, Selim (Computer animation and virtual worlds, 2025)
ABSTRACT As Extended Reality (XR) technologies continue gaining popularity, various domains seek to integrate them into their workflows to enhance performance and user satisfaction. However, integrating XR technologies into emergency response presents unique challenges. Unlike other fields, such as healthcare, entertainment, or education, emergency response involves physically demanding environments and information‐intensive tasks that first responders (FRs) must perform. Augmented reality (AR) head‐mounted displays (HMDs) present promising solutions for improving situational awareness and reducing the cognitive load of the FRs. However, limited research has focused on the specific needs of FRs. Moreover, existing studies investigating FR needs have primarily been conducted in controlled laboratory settings, revealing a significant gap in the literature concerning FR requirements in real‐life scenarios. This work addresses this gap through a comprehensive user study with subject matter experts (SMEs) and FRs. User studies were conducted after two different real‐life scenarios using AR HMDs. To further understand FR needs, we extensively reviewed the literature for similar studies that reported FR needs, explicitly focusing on studies including interviews with SMEs and FRs. Our findings identified key design guidelines for FR‐friendly AR interfaces while also highlighting the direction for future research to improve the user experience of the FRs. As Extended Reality (XR) technologies continue gaining popularity, various domains seek to integrate them into their workflows to enhance performance and user satisfaction. However, integrating XR technologies into emergency response presents unique challenges. Unlike other fields, such as healthcare, entertainment, or education, emergency response involves physically demanding environments and information‐intensive tasks that first responders (FRs) must perform. Augmented reality (AR) head‐mounted displays (HMDs) present promising solutions for improving situational awareness and reducing the cognitive load of the FRs. However, limited research has focused on the specific needs of FRs. Moreover, existing studies investigating FR needs have primarily been conducted in controlled laboratory settings, revealing a significant gap in the literature concerning FR requirements in real‐life scenarios. This work addresses this gap through a comprehensive user study with subject matter experts (SMEs) and FRs. User studies were conducted after two different real‐life scenarios using AR HMDs. To further understand FR needs, we extensively reviewed the literature for similar studies that reported FR needs, explicitly focusing on studies including interviews with SMEs and FRs. Our findings identified key design guidelines for FR‐friendly AR interfaces while also highlighting the direction for future research to improve the user experience of the FRs.